Obscenity, Pornography, Morality: Moral Power as Carnal Resonance - Cardoso, Daniel (2021)
This commentary focuses on the cinematic and intellectual work of Miguel De, expressed through The Kiss and its accompanying essay. The objective here is to problematize some of the historical and technocultural connections raised by the essay, and to frame De’s experimental essay film within a wider tradition of (mostly European) film-making who has as its main aim a troubling of the notion of “pornography”. This troubling is often done through a double deployment of vision: the audience is shown a named something, but maybe not what they were expecting to see, and it is through the disconnect between the naming and the showing that the connections between sexuality, obscenity and carnal resonance are made apparent and contingent. However, as these acts of troubling circulate within the contemporary technological capitalist mediasphere, they quickly become a locus for a potential site of capture, normalization and redeployment of power relationships.